A convenient one-pot synthesis of 1-aryl-substituted 2H-isoquinolin-3-ones - Méndez, Leticia J. (2012)
The synthesis of 1-aryl-substituted 2H-isoquinolin-3-ones is studied from 2-cyanomethylbenzoic acid and substituted benzenes via Friedel–Crafts acylation and intramolecular cyclization of 2-acylphenylacetonitriles formed in a one-pot method using sulfated zirconia as catalysts. Short reaction times, simplicity of operation, and easy work-up are some advantages of this method.